2012
DOI: 10.1002/srin.201200092
|View full text |Cite
|
Sign up to set email alerts
|

Study on Properties of Alumina‐Based Mould Fluxes for High‐Al Steel Slab Casting

Abstract: During the continuous casting of high‐Al steel, the dynamic reduction of silica‐based mould fluxes by the aluminium in the steel leads to changes in their composition and physical properties. The alumina‐based mould flux has been suggested as an alternative to alleviate this reduction problem. However, until now, the smooth running of high‐Al steel continuous casting has been impeded by the lack of systematic investigation of properties of this slag. In this paper, the effects of typical components on the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 5 publications
(5 reference statements)
2
35
1
1
Order By: Relevance
“…The melting temperature increased higher with an excessive content of Li 2 O around exceeding 14 wt%, fluxing action of Li 2 O become unobvious for the precipitation of LiAlO 2 . Similar results were also obtained by Wu et al, they investigated the melting temperature of the CaO–Al 2 O 3 –MgO–B 2 O 3 –SiO 2 –Li 2 O–CaF 2 system, results show that the melting temperature reached its lowest points when the content of Li 2 O was 7 wt%, and an abrupt turn happened with a further increase in Li 2 O content. They also suggested that in the Li 2 O additive increased to 8 wt% promoted the precipitation of LiAlO 2 at high temperatures and lead to the increases in melting temperature.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The melting temperature increased higher with an excessive content of Li 2 O around exceeding 14 wt%, fluxing action of Li 2 O become unobvious for the precipitation of LiAlO 2 . Similar results were also obtained by Wu et al, they investigated the melting temperature of the CaO–Al 2 O 3 –MgO–B 2 O 3 –SiO 2 –Li 2 O–CaF 2 system, results show that the melting temperature reached its lowest points when the content of Li 2 O was 7 wt%, and an abrupt turn happened with a further increase in Li 2 O content. They also suggested that in the Li 2 O additive increased to 8 wt% promoted the precipitation of LiAlO 2 at high temperatures and lead to the increases in melting temperature.…”
Section: Resultssupporting
confidence: 86%
“…Considering of the effects on environment, fluxes such as CaF 2 and NaF were eliminated to avoid fluoric contaminants. Besides the weakest reactivity of Li 2 O, reported researches show that Li 2 O has a strong fluxing action, with a 1 wt% increase in the content of Li 2 O, the melting temperature of conventional mold fluxes decreased by 60 °C on average. Taking the reactivity and the fluxing action into account, Li 2 O was selected as fluxing agent.…”
Section: Design Of New Mold Fluxmentioning
confidence: 99%
“…[2][3][4] In order to solve the problem on chemical composition change of mould fluxes and develop optimal mould flux to meet the requirements of the high aluminum steel casting, previous researchers have proposed the nonreactive CaOAl 2 O 3 based mould flux to substitute for conventional limesilica-based mould fluxes. 2,[5][6][7][8][9][10][11] Blazek et al 7) developed lime-alumina-based mould flux for casting high aluminum TRIP steel. The interaction between flux and steel was markedly reduced and the as-cast slab quality was improved compared with lime-silica-based mould flux.…”
Section: Introductionmentioning
confidence: 99%
“…The results are shown in the following discussions. [24][25][26] show that Li ion, which has the minimum ionic radius, has just one positive charge, implying Li + could freely move in the space of [AlO 4 ]-tetrahedrons and Li + ions have the priority to compensate the highly-polymerized [AlO 4 ]-tetrahedrons. Moreover, ionic bonds between cations and anions also exist in the molten slag, such as Ca-O ionic bond and Ce-O ionic bond.…”
Section: Crystallization Process Of the Mold Fluxesmentioning
confidence: 99%